The combined application of organic and inorganic fertilizers increases soil organic matter and improves soil microenvironment in wheat-maize field - Yang, Qinglong; Zheng, Fengxia; Jia, Xucun; Liu, Peng; Dong, Shuting; Zhang, Jiwang; Zhao, Bin (Journal of soils and sediments, 2020)
Purpose This long-term study used a lysimeter platform to monitor the changes of organic matter and total nitrogen content in deep soils of various fertilization treatments of wheat-maize in the Huanghuaihai area, with the goal to improve the soil environment and increase the quantity and diversity of soil microbes, and then provide a theoretical basis for synergetic improvement of production and resource utilization efficiency. Materials and methods The experiment included a no-N-fertilizer treatment as a control (CK) to study the following three fertilizer treatments: the exclusive application of urea (U), the exclusive application of cattle manure (M), and the combined application of organic and inorganic fertilizers (UM). Results and discussion These results showed that fertilization significantly increased the soil organic matter content. Compared with CK, the average soil organic matter content of each soil layer treated with M, UM, and U was increased by 25.00%, 22.81%, and 8.96% in wheat growing season, respectively. The average soil organic matter content of each soil layer in the 2-year average M, UM, and U treatments increased by 148.70%, 16.81%, and − 7.18% maize growing season, respectively. In the 2-year wheat field, in the 0–20 cm soil layer, the effects of each treatment on the total nitrogen content of the soil were significant, and compared with the CK treatment, the UM, M, and U treatments increased by 105.72%, 75.07%, and 47.13%. For maize field, compared with the CK treatment, the total nitrogen content of M, UM, and U increased by 83.34%, 50.27%, and 7.10%. The addition of organic fertilizer can increase the number and diversity of bacteria and fungi in the soil, and the application of urea significantly reduced the quantities and diversities of bacteria. The combined application of organic and inorganic fertilizers can increase the number and diversity of soil actinomycetes. The combined application of organic and inorganic fertilizers could significantly increase the number of maize roots. Compared with CK treatment, the number of roots increased by 66.67%. After long-term experimental treatment, the yields of wheat and maize were all expressed as UM > U > M > CK. Conclusions The combination of organic and inorganic N fertilizers increased the soil organic matter content, improved the soil environment, increased the quantity and diversity of soil microbes, promoted the growth and development of crop roots, and increased the yield of wheat and maize. It was a reasonable fertilization method to synergistically improve the production and resource utilization efficiency.